The Effectiveness of Cognitive Empowerment Based on the Lumosity Program on Maher Crystallized Intelligence of Elementary School Boys - Ershadi Chahardeh, Shima; Saadati Shamir, Abutaleb; Zabihi, Rozita (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to evaluate the effectiveness of cognitive empowerment based on the Lumosity program in enhancing Maher crystallized intelligence of elementary school boys. Methods and Materials: The research was conducted using a quasi-experimental design with pre-test, post-test, and follow-up stages, along with control and experimental groups. A sample of 40 male elementary students was randomly selected and divided into control and experimental groups. The experimental group underwent cognitive training using the Lumosity program, while the control group received no intervention. Intelligence was assessed using standardized tests across multiple components of intelligence, including personality-emotional, social-cultural, bodily-kinesthetic, happiness, and crystallized intelligence. Data analysis involved repeated measures ANOVA to compare intelligence scores across groups and time points. Findings: The results revealed no significant improvement in personality-emotional intelligence, social-cultural intelligence, bodily-kinesthetic intelligence, happiness intelligence, or crystallized intelligence in the experimental group following the Lumosity-based cognitive empowerment program. Despite improvements in processing speed and attention, the training did not effectively enhance the targeted intelligence components. Factors such as the nature of the tasks, which emphasized processing speed over knowledge acquisition, and the program’s lack of focus on real-life applications and social-cultural skills may have limited its impact. Conclusion: The findings suggest that while the Lumosity-based cognitive empowerment program may enhance cognitive processing abilities, it does not significantly improve the broader dimensions of intelligence.